Stent angioplasty to relieve left pulmonary artery obstruction caused by patent ductus arteriosus device occlusion. Issue 3 (8th March 2013) - Dean, Peter N.; Slack, Michael C.
<x xml:space="preserve">Abstract</x> A 7‐month‐old patient in congestive heart failure due to a moderate sized patent ductus arteriosus (PDA) underwent uncomplicated implantation of an Amplatzer Ductal Occluder (ADO1). Two months after percutaneous device PDA closure, left pulmonary artery (LPA) stenosis was discovered. Rather than spontaneous improvement as reported in previous cases, our patient's LPA stenosis progressed in severity 7 months after ADO1 placement. A catheterization demonstrated a 32 mm Hg peak gradient from her main pulmonary artery to her LPA. She underwent successful stent angioplasty of her LPA with an excellent result and preserved PDA closure. This case demonstrates that stent angioplasty is a feasible an effective method of relieving LPA obstruction caused by a PDA occluder device. Additionally, despite slight deflection by the stent, the ADO1 device continued to provide complete ductal closure. Stent angioplasty should be considered in patients who have LPA stenosis caused by ADO1 occluder device that does not improve over time. © 2013 Wiley Periodicals, Inc.